Cardiac Leiomyosarcoma in a Cat Presenting for Bilateral Renal Neoplasia. (April 2019) - Schreeg, M.E.; Evans, B.J.; Allen, J.; Lewis, M.C.; Luckring, E.; Evola, M.; Richard, D.K.; Piner, K.; Thompson, E.M.; Adin, D.B.; Tokarz, D.A.
Summary: A 10-year-old neutered female domestic longhair cat was presented to a tertiary care veterinary hospital for evaluation of a right renal mass that was identified incidentally on abdominal radiographs and classified further as a sarcoma based on fine needle aspiration cytology. Further diagnostic workup, including ultrasound and cytology, identified a sarcoma in the left kidney. After approximately 1 month of conservative medical management, the clinical condition deteriorated and the cat was humanely destroyed. Post-mortem examination confirmed bilateral renal masses with multifocal infarction and extensive necrosis, and further identified a large mass at the apex of the heart as well as multiple pulmonary nodules. Microscopical examination of the masses identified a population of poorly-differentiated neoplastic spindle cells, consistent with sarcoma. Immunohistochemically, the neoplastic cells expressed smooth muscle actin and muscle-specific actin, but were negative for myoglobin and factor VIII. Phosphotungstic acid–haematoxylin staining was unable to identify cross-striations in the neoplastic cells. Based on these results and the pattern of lesion distribution, the cat was diagnosed with cardiac leiomyosarcoma with pulmonary and bilateral renal metastasis.